Macrophage‐like Cells Are Responsive to Titania Nanotube Intertube Spacing—An In Vitro Study - Necula, Madalina Georgiana; Mazare, Anca Valentina; Negrescu, Andreea Mariana; Mitran, Valentina; Özkan, Selda; Trusca, Roxana; Park, Jung; Schmuki, Patrik; Cimpean, Anisoara (International Journal of Molecular Sciences, 2022)
With the introduction of a new interdisciplinary field, osteoimmunology, today, it is well acknowledged that biomaterial‐induced inflammation is modulated by immune cells, primarily macrophages, and can be controlled by nanotopographical cues. Recent studies have investigated the effect of surface properties in modulating the immune reaction, and literature data indicate that various surface cues can dictate both the immune response and bone tissue repair. In this context, the purpose of the present study was to investigate the effects of titanium dioxide nanotube (TNT) interspacing on the response of the macrophage‐like cell line RAW 264.7. The cells were maintained in contact with the surfaces of flat titanium (Ti) and anodic TNTs with an intertube spacing of 20 nm (TNT20) and 80 nm (TNT80), under standard or pro‐inflammatory conditions. The results revealed that nanotube interspacing can influence macrophage response in terms of cell survival and proliferation, cellular morphology and polarization, cytokine/chemokine expression, and foreign body reaction. While the nanostructured topography did not tune the macrophages’ differentiation into osteoclasts, this behavior was significantly reduced as compared to flat Ti surface. Overall, this study provides a new insight into how nanotubes’ morphological features, particularly intertube spacing, could affect macrophage behavior.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Cytokines; Inflammation; Intertube spacing; Macrophage; Osteoclastogenesis; TiO2 nanotubes